Implementation of Mikrotik Firewall and QoS for Secure and Efficient Internet Networking - Seyhan; Triloka, Joko (Universitas Negeri Padang, 2025)
Effective network management in school environments is an ongoing challenge as the demand for internet access among students, teachers, and staff continues to grow. This study aims to design and implement a Mikrotik-based network management solution. The research was conducted at SMK Negeri 1 Bandar Lampung, with the objectives of improving network service quality, optimizing bandwidth allocation, and ensuring network security. Mikrotik was chosen due to its flexibility in network management at a relatively affordable cost. The research methods included analyzing the school’s network requirements, designing the network topology, and configuring Mikrotik devices based on Quality of Service (QoS), firewall, and user access control. The results show that the implementation of Mikrotik successfully enhanced network stability, reduced latency, and restricted access to non-relevant websites. These findings highlight that Mikrotik provides an effective and efficient solution for network management, particularly in small to medium-scale settings. This study is expected to serve as a reference for other schools facing similar challenges in network management.